Binding of Monovalent and Bivalent Ligands by Transthyretin Causes Different Short- and Long-Distance Conformational Changes - Corazza, Alessandra (J Med Chem, 2019)
[Image: see text] The wild type protein, transthyretin (TTR), and over 120 genetic TTR variants are amyloidogenic and cause, respectively, sporadic and hereditary systemic TTR amyloidosis. The homotetrameric TTR contains two identical thyroxine binding pockets, occupation of which by specific ligands can inhibit TTR amyloidogenesis in vitro. Ligand binding stabilizes the tetramer, inhibiting its proteolytic cleavage and its dissociation. Here, we show with solution-state NMR that ligand binding induces long-distance conformational changes in the TTR that have not previously been detected by X-ray crystallography, consistently with the inhibition of the cleavage of the DE loop. The NMR findings, coupled with surface plasmon resonance measurements, have identified dynamic exchange processes underlying the negative cooperativity of binding of “monovalent” ligand tafamidis. In contrast, mds84, our prototypic “bivalent” ligand, which is a more potent stabilizer of TTR in vitro that occupies both thyroxine pockets and the intramolecular channel between them, has greater structural effects.